Family family : a novel - Frankel, Laurie (Henry Holt and Company, 2024)
"India Allwood grew up wanting to be an actress. Armed with a stack of index cards and a hell of a lot of talent, she goes from awkward 16-year-old to Broadway ingenue to tv star. But while promoting her most recent project, a film about adoption, India does what you should never do - she tells a journalist the truth: it's a bad movie. Like so many movies about adoption, it tells only one story, a tragic one. But India's an adoptive mom herself and knows there's so much more to her family than tragedy. Soon she's at the center of a media storm, battling accusations from the press and the paparazzi, from protesters on the right and advocates on the left. Her daughter Fig knows they need help - and who better to call for help than family? Because India's not just an adoptive mom. She also had a baby she gave up for adoption her senior year of high school. That baby is now sixteen, excited to meet her birth mother and eager to help, but she also has an agenda and secrets of her own. It turns out what makes a family isn't blood and it isn't love because no matter how they're formed, the hallmark of true family is this: it's complicated"--